Practicing Poverty and Spirit in the First Beatitude of Matthew's Gospel - Sykes, Jesse (Trinity College Dublin.School of Religion, Theology, and Peace Studies, 2026)
This study examines the meaning of poor in spirit in the first beatitude (Matt 5:3) by addressing a lacuna in research on the Matthean beatitudes that prioritizes discussion on the literal or metaphoric nature of poverty while ignoring spirit. This preoccupation with the type of poverty at the expense of spirit in the first beatitude is reflected in the divide between interpretations that understand poor in spirit as a virtue or as a condition. Attention to spirit in the Second Temple suggests that the first beatitude (and by extension the rest) is better understood in terms of embodied practice. Spirit in the Second Temple period takes on new significance, especially in terms of mapping the self and the liminal intersection between the human and inhuman, the mundane and transmundane. During the same period economic language takes on increased importance as wealth and poverty demarcate the boundaries between the consequences of wise and unwise behavior. Chapters 2 and 3 examine economic and spirit language, noting an important point of convergence in what this study refers to as the idiom of the commoditized self, whereby mundane activity comes to have transmundane consequences, and moral failure may cost the inestimable price of one's spirit or soul. This idiom is found in two key texts for examining both spirit and poverty in Matt 5:3: the wisdom text 4QInstruction and the Hodayot (1QHa). It is also found in the gospel of Matthew (Matt 16:26). Chapter 4 examines poverty and spirit in 4QInstruction and notes the importance of poverty in shaping various practices of reproof and forgiveness. 4Q417 2 i 1-16 shares important intertexts with Matt 5:3 and 18:15-18 that suggests that poverty and spirit may have operated in analogous ways for both 4QInstruction and the gospel of Matthew in terms of practices of reproof and forgiveness. Chapter 5 ends with an examination of the Hodayot and the gospel of Matthew, concluding that poor in spirit refers to an embodied practice rooted in the gospel's moral economy and reflected in a communitas related to such important procedures as reproof and forgiveness.
APPROVED
Keywords: 4QInstruction; Gospel of Matthew; Poor in Spirit